Accelerated Screening of Thermoelectric Materials by First‐Principles Computations of Electron–Phonon Scattering. Issue 20 (20th April 2018) - Samsonidze, Georgy; Kozinsky, Boris
Abstract: Recent discoveries of new materials for thermoelectric energy conversion are enabled by efficient prediction of the materials' performance from first‐principles, without empirically fitted parameters. The novel simplified approach for computing electronic transport properties is described, which achieves good accuracy and transferability while greatly reducing complexity and computation cost compared to the existing methods. The first‐principles calculations of the electron–phonon coupling demonstrate that the energy dependence of the electron relaxation time varies significantly with chemical composition and carrier concentration, suggesting that it is necessary to go beyond the commonly used approximations to screen and optimize materials' composition, carrier concentration, and microstructure. The new method is verified using high accuracy computations and validated with experimental data before applying it to screen and discover promising compositions in the space of half‐Heusler alloys. By analyzing data trends the effective electron mass is identified as the single best general descriptor determining material' performance. The Lorenz number is computed from first principles and the universality of the Wiedemann–Franz law in thermoelectrics is discussed. Abstract : An efficient approach for first‐principles prediction of thermoelectric transport is introduced and used to calculate electronic transport properties of semiconductors, starting from energy‐dependent electronic relaxation times due to electron–phonon scattering. The method enables computational screening of a wide range of half‐Heusler alloy compositions and discovery of new material compositions. Electron effective mass is identified as a general classifier of thermoelectric performance.